Geographical Analysis of Population Growth in Kalar District Between (1977-2022) (Raparin Journal of Humanities (RJH), 2025)
The growth of the population can be assumed as one of the significantly paramount demographic phenomena in the field of population geography, which has impacts upon the dynamic face of society from past, present, and in the future as well, opening windows of opportunities to the planners with all the required information to build general outlines of the development planning in all the variety of life, economy, construction, and health sectors. Therefore, population growth turned out to be an accentuated phenomenon by the population geographers.This study highlights the population growth of Kalar district during the years 1977-2022. Kalar district is one of the most remarkably outstanding districts in the Kurdistan Region overall and Sulaimani province in particular, situated at the southeast of Sulaimani province as it incorporates 4 instrumental administrative units.The objective of this research is to render the distinction in population growth in the area of investigation. The result of this research revealed that the percentage of natural increase in the area of investigation between the years of 2010-2022 was (16.4%). The highest rate in the year of 2013 was (100.0%) (24.3%), while the lowest of all was (10.6%) in the year of 2020. This research concludes that population growth in various areas of investigation fluctuates as per the years in question. The growth of the population between the years of 1977-2002 in the area of investigation reached (5.4%), whilst in Sulaimani province it was (3.5%). However, in the years 2002-2022, the growth rate in the area of investigation decreased to (2.5%), while the growth of the population in Sulaimani province was (1.7%)